Comparative characteristics of operating systems of the windows 7th and 10th generations family - Kadirova Gulchehra; Rasuleva Maprat; Khalilova Shoira; Akbarov Nurislom Akhtamjon ugli (International Journal on Human-Computing Studies, 2021)
The article reveals the concept and essence of operating systems, describes the functions of operating systems, provides statistics on the most popular operating systems among the Windows family, describes the characteristics and features of Windows 7 and Windows 10 operating systems, conducts a comparative analysis of the characteristics and draws conclusions.